The implementation of learning guidance with instructional media to increase interest in learning literacy and numeracy - Ningrum, Diana Nazifa (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2023)
A new learning method is needed to increase participants' interest in numeracy students in the UPTD SD Negeri 3 Kerticala. More than learning methods commonly used in class is required to foster student interest and enthusiasm. This research aims to use simple learning media in tutoring. This research was conducted on 33 grades 3-5 students at UPTD SD Negeri 3 Kerticala. A descriptive qualitative approach was used in this study, and students received simple learning media through a direct-action process. This study had limitations: it was conducted only a few times in each class and had no evaluation phase, but the results were interesting. This study found that using simple learning media increased students' interest in learning, especially in learning numeracy. This research also shows that exciting and different learning media can positively influence learning interest. Students also show increased enthusiasm, interest, and motivation to learn after using the learning media.